Polycondensation of Acid anhydrides with Asparaginyl Imide Diamine and Curing with Styrene as Smart Polymers for Sustained Release Drug Delivery System - M.A, Firyal; Aziz Rahi, Firas; Q. M, Assel; I. alshather, Ahmed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Polymers can provide new and effective ways of administering drugs and enhance therapeutic efficacy. Polymers also present a means for controlled delivery of several drugs in the form of polymeric drug carriers or polymeric prodrugs. Our study involved synthesize of new condensed polymers from reacting of unsaturated acid anhydride such as maleic or methylnadic anhydrides, with prepared N-asparaginyl imide diamine, which prepared from reacting of asparaginyl chloride with ammonia. The new condensed polymers were curing with styrene and the cross-linked polymers were obtained with high conversion percent. The physical properties were measured and all the prepared monomers and polymers were characterized by FT-IR and UV spectroscopy. The intrinsic viscosity was calculated and swelling index was measured for the prepared cross-linked polymers. The inserted asparagine as amino acid could enhance the biodegradability properties, and these prepared bioactive polymers can be used as biomaterial in different applications, which could be acted as smart polymers due to pH sensitivity.